A Multi-Institutional Analysis of Prostate Cancer Patients With or Without 68Ga-PSMA PET/CT Prior to Salvage Radiotherapy of the Prostatic Fossa - Schmidt-Hegemann, Nina-Sophie; Zamboglou, Constantinos; Thamm, Reinhard; Eze, Chukwuka; Kirste, Simon; Spohn, Simon; Li, Minglun; Stief, Christian; Bolenz, Christian; Schultze-Seemann, Wolfgang; Bartenstein, Peter; Prasad, Vikas; et al. (Frontiers in Oncology, 2021)
Introduction: 68Ga-PSMA PET/CT is associated with unprecedented sensitivity for localization of biochemically recurrent prostate cancer at low PSA levels prior to radiotherapy. Aim of the present analysis is to examine whether patients undergoing postoperative, salvage radiotherapy (sRT) of the prostatic fossa with no known nodal or distant metastases on conventional imaging (CT and/or MRI) and on positron emission tomography/computed tomography (68Ga-PSMA PET/CT) will have an improved biochemical recurrence-free survival (BRFS) compared to patients with no known nodal or distant metastases on conventional imaging only. Material and Methods: This retrospective analysis is based on 459 patients (95 with and 364 without 68Ga-PSMA PET/CT). BRFS (PSA < post-sRT Nadir + 0.2 ng/ml) was the primary study endpoint. This was first analysed by Kaplan-Meier and uni- and multivariate Cox regression analysis for the entire cohort and then again after matched-pair analysis using tumor stage, Gleason score, PSA at time of sRT and radiation dose as matching parameters. Results: Median follow-up was 77.5 months for patients without and 33 months for patients with 68Ga-PSMA PET/CT. For the entire cohort, tumor stage (pT2 vs. pT3-4; p= <0.001), Gleason score (GS≤7 vs. GS8-10; p=0.003), pre-sRT PSA (<0.5 vs. ≥0.5ng/ml; p<0.001) and sRT dose (<70 vs. ≥70Gy; p<0.001) were the only factors significantly associated with improved BRFS. This was not seen for the use of 68Ga-PSMA PET/CT prior to sRT (p=0.789). Matched-pair analysis consisted of 95 pairs of PCa patients with or without PET/CT and no significant difference in BRFS based on the use of PET/CT was evident (p=0.884). Conclusion: This analysis did not show an improvement in BRFS using 68Ga-PSMA PET/CT prior to sRT neither for the entire cohort nor after matched-pair analysis after excluding patients with PET-positive lymph node or distant metastases a priori. As no improved BRFS resulted with implementation of 68Ga-PSMA PET in sRT planning, sRT should not be deferred until the best “diagnostic window” for 68Ga-PSMA PET/CT.